Decision support tool to mitigate ship-induced erosion in non-uniform, sheltered coastal fairways. (15th June 2022) - Almström, Björn; Larson, Magnus; Hallin, Caroline
Abstract: The negative impact of maritime traffic in terms of shore erosion in sheltered coastal fairways can be mitigated by sustainable fairway management. Mitigation measures include regulating the ship traffic in terms of speed, routes, or size of ships, but can also involve erosion protection along a fairway. For effective shoreline management of a fairway, it is essential to predict ship waves, to identify sites with potential erosion problems, and to investigate the effectiveness of different measures before implementing them. Several attempts have been made to develop site-specific criteria for managing ship waves. However, few available generic models consider primary waves generated by large ships in confined fairways. Therefore, a tool for supporting decisions in fairway management was developed. The decision support tool is based on simplified formulas for ship- and wind-wave prediction, combined in a framework that enables automatic, rapid assessments on large spatial and temporal scales. Moreover, the tool requires only readily available input data, such as data on AIS, bathymetry, shoreline geometry, wind, fairway centreline, and grain size. The output from the model includes ship and wind wave heights and potential erosion sites. The decision support tool was applied to the Furusund Fairway, Sweden, by simulating one year of ship traffic to validate its capability of identifying potential erosion sites. The simulation demonstrated that the tool was capable of identifying known erosion sites in the fairway. Additionally, scenarios with different speed regulation strategies for the Furusund Fairway were investigated using the decision support tool. Overall, it is concluded that the developed tool enables rapid assessment of ship waves, wind waves, and potential erosion over large areas in fairways. Highlights: Managing fairway shorelines require an understanding of the impact of ship waves. The developed tool uses open-access data and existing equations for ship waves. When applied to an intra-coastal fairway, the tool identified erosional hot spots. Scenario simulations showed the effectiveness of various fairway management options. The simplicity and agility of the tool will be useful for fairway managers.